Renegotiating literary culture in contemporary film adaptations of Jane Austen's Mansfield Park and Emma - Levin, Adam (My University, 2012)
In this dissertation I will be examining two contemporary film adaptations of Jane Austen’s novels. The films in question are Amy Heckerling’s 1995 mainstream youth film Clueless, an adaptation of Emma (1816), and Whit Stillman’s 1990 art-house film Metropolitan, an adaptation of Mansfield Park (1814). Each film’s contemporary approach to Austen’s work significantly alters the narratives of their respective source texts. Hence, it is difficult for us to associate them directly with the world Austen presents to us in her novels. However, as I will argue, the manner in which these films remove Austen from her context illuminates her critique of literary culture. Austen’s work is preoccupied with the status and reception of the literature of her era and her narratives critique our own responses to this literature. By bringing this critique into the modern era, Clueless and Metropolitan formulate a dialogue with their source texts. This dialogue highlights the relevance of this critique within our contemporary context. Furthermore, it allows Clueless and Metropolitan the opportunity to assess the way in which we read Austen’s work within a contemporary modality. By exploring the dialogue which occurs between the Austen’s novels and these films, I will address the broader claim that the process of adaptation is not linear. Rather, it is a dialogic process which promotes a constant interchange between the adapted text and the film adaptation.
M.A. Uiversity of the Witwatersrand, Faculty of Humanities, 2012